What do we know about the future of agri-food systems in Eastern and Southern Africa? - Tesfaye, Kindie; Hartley, Faaiqa; Thomas, Timothy S.; Gbegbelegbe, Sika; Gabriel, Sherwin (CGIAR System Organization, 2022)
Key messages - Food demand in Eastern and Southern Africa (ESA) is expected to be 3 to 9 times higher by 2050 (relative to 2010) depending on the emerging economic and demographic trends. - To meet demand, agri-food systems (AFS) in the region must expand and diversify. Consumption demand for meats and fruits and vegetables will more than double by 2050. These shifts create economic opportunities but also inclusivity challenges. - Transformations in the AFS must increase the sector’s resilience to supply-side shocks which threaten food security and nutrition. By 2050, climate change could increase the number of people at risk of hunger by between 13.3 and 30.5 million. - Favorable policies and investments that are country specific, inclusive, and sustainable will be powerful tools to shape and influence the AFS transition in the region.